EFFECTS OF SOCIO-ECONOMIC DEVELOPMENT CHALLENGES ON RURAL COMMUNITIES IN NIGERIA: A EXPOSITORY STUDY OF ODUGBO COMMUNITY IN APA LGA OF BENUE STATE, NIGERIA - Echeonwu, Macdonald Silas; Amough, John Mercy (Journal of Social Science, 2025)
Objective: Rural communities in Nigeria face various socio-economic development challenges that hinder their progress and well-being. This study examines the effects of these challenges, particularly in Odugbo community, located in Apa Local Government Area of Benue State, Nigeria. The research aims to identify key socio-economic barriers and propose strategies for sustainable development. Method: This study is based on the Social Capital Theory and employs a mixed-methods approach, combining both qualitative and quantitative research. Primary data were collected through questionnaires administered to 350 randomly selected participants, including community members and relevant stakeholders. Secondary data were obtained from literature, reports, and other documentary sources. The mean scores were used for analyzing research questions, while content analysis was applied to secondary data. Results: Findings indicate that inadequate infrastructure, limited access to healthcare and education, poor road networks, high poverty rates, and limited economic opportunities are significant socio-economic challenges in the Odugbo community. The study also highlights various strategies to address these issues, including community engagement, access to financial services, external support and partnerships, government policies, and awareness creation. Novelty: This study contributes to existing literature by providing an in-depth analysis of socio-economic challenges in a specific rural Nigerian community and proposing localized strategies for sustainable development. The findings emphasize the importance of community-driven initiatives and external collaborations to overcome socio-economic barriers.